Analise topografica de bacias de drenagem - Christofoletti, A. (My University, 1986)
The morphometric analysis has a long history and the authors list 26 indices. -after English summary
Topographic analysis applied to drainage basins
Keywords: drainage basin; morphometric analysis; topographic analysis